2017
DOI: 10.1016/j.soard.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The utility of weight loss medications after bariatric surgery for weight regain or inadequate weight loss: A multi-center study

Abstract: Background: Patients who undergo bariatric surgery often have inadequate weight loss or weight regain. Objectives: We sought to discern the utility of weight loss pharmacotherapy as an adjunct to bariatric surgery in patients with inadequate weight loss or weight regain. Setting: Two academic medical centers. Methods: We completed a retrospective study to identify patients who had undergone bariatric surgery in the form of a Roux-en-Y gastric bypass (RYGB) or a sleeve gastrectomy from 2000– 2014. From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 46 publications
6
114
0
5
Order By: Relevance
“…For patients who do have weight regain after achieving a healthier body mass index or with inadequate weight loss, pharmacotherapy may be an option for postoperative patients to achieve a healthy weight. 30 …”
Section: Discussionmentioning
confidence: 99%
“…For patients who do have weight regain after achieving a healthier body mass index or with inadequate weight loss, pharmacotherapy may be an option for postoperative patients to achieve a healthy weight. 30 …”
Section: Discussionmentioning
confidence: 99%
“…After bariatric surgery, anti-obesity drugs are usually started when weight regain ensues. Prescribing weight loss pharmacotherapy before weight regain occurs (at weight plateau) may result in greater amount of total weight loss from the pre-operative period [159] and may prevent weight regain. A recent retrospective review demonstrated that phentermine alone and a phentermine-topiramate combination, in addition to diet and exercise, appear to be viable options for weight loss in RYGB and adjustable gastric banding patients who experienced weight recidivism or weight loss plateau [160].…”
Section: Weight Regain Prevention and Managementmentioning
confidence: 99%
“…[ [16][17][18] Conversely, other patients may develop significant malnutrition when there is not enough absorption of key nutrients [19][20][21] which may even lead to a functional short bowel syndrome which despite its rarity is a far more severe complication and can occur more frequently the shorter the CL length is.…”
Section: Authors' Contributionsmentioning
confidence: 99%